MAKNA DAN FUNGSI ADMINISTRASI PENDIDIKAN DI ERA DIGITAL PADA JENJANG MI/SD - Ahmad Tarmizi Hasibuan; Fani Anggita Lubis; Nurul Rizki Amalia; Dalilah Awanis (ABDAU : Jurnal Pendidikan Madrasah Ibtidaiyah, 2023)
This thesis examines the field of educational administration, particularly with regard to the skill and competency requirements of education administrators in the information age shaped by digital technology. The purpose of this paper is to provide an overview of the skills that must be mastered by administrators in the field of educational administration in the midst of very rapid technological developments. The methodology used in this study is qualitative-descriptive and based on a literature review. The data in this study were collected through documentation techniques from various important sources regarding the topic. The results of the study conclude that in this digital era, there are great benefits in information access and connectivity, but also new challenges related to information reliability, privacy and data security. It is important for individuals and communities to use digital technology wisely and be aware of its impact, and to face the challenges of the digital era with effective and responsive efforts.